Présence transactionnelle et dimensions du soutien aux apprenants dans la formation à distance au secteur des jeunes. Retour sur une première année d'expérimentation - Alexandre Lanoix; Serge Gérin-Lajoie; Marc-André Éthier; Bruno Poellhuber; Normand Roy (Université de Provence, 2022)
The article presents the first results of a research aimed at distance learning in the youth sector in social studies courses of the second cycle of secondary education in Quebec. The research relies on the concept of transactional presence and the dimensions of student support in distance learning and shows that according to the teachers, students seem to be going through motivational difficulties. At the same time, teachers have a hard time creating a strong presence to help the students.